THE EFFECTIVENESS OF MIXED MEDIA PAINTING ACTIVITIES ON IMPROVING CHILDREN’S FINE MOTOR SKILLS AT SBB AL-MANNAN PALOH KINDERGARTEN NORTH ACEH DISTRICT 20 - Darmiah; Mesrida Simarmata; Indra Agussamad; Nur azizah; Indra Manurung; Wahyuni (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Motor development is a process of maturity or movement that directly involves muscles to move and a neural process that enables a person to move their body. WHO states that 20-40% of children experience delays, while Indonesia reaches 16%. One method that can be used to meet the needs for motor development is by stimulating through the drill method in Mixed Media painting activities. The aim of this research is to see that the treatment carried out can improve the motor development of children aged 3-5 years at SBB Al-Mannan Paloh Kindergarten. This research design uses a Pre- Experimental Design with a One Group Pretest-Posttest Design. The population in this study were all children aged 3-5 years with a sampling technique using Non Probability Sampling selected using Perposive Sampling consisting of 30 respondents. The variable measured in this research is the child’s fine motor development. This study used the Wilcoxon signed rank test (a<0.05). The results of the study showed that the increase in children’s fine motor skills after the painting activity was higher than before. with p value = 0.003. Thus, it can be concluded that the hypothesis is accepted, meaning that there is an influence of the activities carried out on improving children’s fine motor skills. It is recommended for health workers to develop promotion and education about mixed media painting activities to the public, especially to parents, to improve children’s fine motor development.